Figurative Language in Ten British Council Learnenglish Kids’ Stories - Riandana, Martinus Hergirico; Bram, Barli (PROJECT (Professional Journal of English Education), 2026)
Figurative language are exposed in British Council LearnEnglish Kids stories. The use of figurative language in the stories required interpretation to understand its literal meaning. Ten stories of British Council LearnEnglish Kids were chosen to be analysed. The objective is to interpret the figurative language into the literal meanings, aiding young readers’ understanding. Descriptive qualitative as a method to write the findings and document analysis as an approach to analyse the data were employed to address the research question. In total, twenty-six figurative language were found in ten printed British Council LearnEnglish Kids stories. Limited figurative language was found since the authors mostly used a direct language to avoid confusion. The figurative language found were eighteen personifications, six hyperboles, one irony, and one apostrophe. Personification is the predominant type of figurative language. This study contributes to help readers, particularly young readers to understand the figurative language available in the stories provided by British Council LearnEnglish Kids website.